Assessing Microglial Dynamics by Live Imaging - Andoh, Megumi; Koyama, Ryuta (Frontiers in Immunology, 2021)
Microglia are highly dynamic in the brain in terms of their ability to migrate, proliferate, and phagocytose over the course of an individual's life. Real-time imaging is a useful tool to examine how microglial behavior is regulated and how it affects the surrounding environment. However, microglia are sensitive to environmental stimuli, so they possibly change their state during live imaging in vivo, mainly due to surgical damage, and in vitro due to various effects associated with culture conditions. Therefore, it is difficult to perform live imaging without compromising the properties of the microglia under physiological conditions. To overcome this barrier, various experimental conditions have been developed; recently, it has become possible to perform live imaging of so-called surveillant microglia in vivo, ex vivo and in vitro, although there are various limitations. Now, we can choose in vivo, ex vivo or in vitro live imaging systems according to the research objective. In this review, we discuss the advantages and disadvantages of each experimental system and outline the physiological significance and molecular mechanisms of microglial behavior that have been elucidated by live imaging.